Structure-function studies of fibronectin domains in the human endometrium - Mok, M; May Mok (2008)
The function of the endometrium is to mediate implantation of the embryo. During the early stages of implantation, the endometrial stroma undergoes differentiation known as decidualization, a process critical for successful embryo implantation. The precise mechanisms involved are not clearly understood but extracellular matrix (ECM) remodelling is a key feature. Fibronectins (FNs) are large glycoproteins abundant in the ECM of the human endometrium. Up to twenty isoforms of FNs are generated from alternative splicing, including the EDIIIA+ and EDIIIB+ variants. This thesis investigated changes in endometrial stromal ECM levels, in particular FN and its splice variants, during decidualization and in response to the endometrial cytokines and growth factors that drive the implantation process. Furthermore, the influence of these splice variants on the functional properties of FN was explored, including cell attachment, spreading and proliferation, integrin binding and focal adhesion kinase activation. Structural studies including crystallization trials were carried out to investigate how the insertion of EDIIIA modulates the conformation of FN and accessibility of its integrin binding sites. These combined studies allow us to test the hypothesis that the regulation of alternative splicing provides a biological mechanism for modulating function of FN in the endometrium. The main findings from this study can be summarized as follows: Immunocytochemistry and immunoblotting demonstrated reduced endometrial stromal levels of EDIIIA+FN, total FN and tenascin during in vitro decidualization. Substrate-associated FN production by endometrial stromal cells was reduced in response to the endometrial cytokine TNFalpha as detected by ELISA. Recombinant FIII7-12A±B± fragments were expressed, purified and mediated endometrial stromal cell adhesion. Inclusion of EDIIIA in the recombinant FIII7-12 fragment decreased binding affinities to integrin alpha5beta1. These findings suggest that production of FNs in the endometrial stroma is modified during in vitro decidualization and in response to endometrial TNFalpha. This modification in ECM composition is likely to result in modulation of cellular processes, perhaps to allow for cellular differentiation and migration that is required for invasion of the implanting embryo.